Measuring the Total Cost of Ankle Fractures: A Prospective Analysis. Issue 4 (22nd October 2020) - Noback, Peter C.; Dougherty, Tess; Freibott, Christina; Swart, Eric F.; Rosenwasser, Melvin P.; Vosseller, J. Turner
Category: Trauma; Ankle Introduction/Purpose: Ankle fractures (AFx) are the most common foot and ankle fracture seen at hospitals in the United States, and are undoubtedly costly to patients. Quantification of the costs of fractures and their associated treatments has garnered increased attention in orthopedics in recent years through cost-effectiveness analysis. However, literature pertaining to AFx's almost never reports on the indirect costs of AFx's, and thus fails to accurately assess the true value of treatments. The purpose of this study was to prospectively assess the direct and indirect costs of AFx's in operatively and nonoperatively treated patients. Secondary analysis included evaluation of the composition of indirect cost, the duration these costs are endured, and the factors that influence their magnitude. Methods: A prospective observational single-center study was performed. Adult patients presenting for initial consult for an AFx that could speak English or Spanish were enrolled. Polytrauma patients and those unable to provide complete indirect cost data were excluded. Patients completed a cost form that asked the money they had spent in the last week on transportation, household chores, and self-care due to their AFx. Patients were considered to have complete indirect cost data if they returned for follow-up visits until they reported no recurring indirect costs and had returned to work. Direct cost data was obtained directly from the hospital billing department. Amount collected was utilized. Direct costs included any costs incurred from staff treating the patient, supplies required for treatment, and the use of healthcare facilities. A descriptive analysis of the entire cohort and stratification by operative status was performed for the primary comparative analysis. Results: 60 patients were ultimately analyzed. Average age was 46.5 years. 55% were female. 10% of patients were diabetic. 17% smoked cigarettes actively. Weber A, B, and C fractures composed 12%, 72%, and 18% of fractures, respectively. Operatively treated patients (n=37) had a significantly higher total and direct cost than non-operative patients (P<0.01). Average salary of the 39 employed patients was $61, 416 and return to work period was 11.2 weeks. In all patients, lost income accounted for the largest portion of total and indirect cost, averaging 38% of total cost. Longer periods of return to work were significantly associated with undergoing surgery and having less than a college-level education (P<0.05). Average number of weeks for indirect costs to amount to zero was 19.1. Conclusion: In patients treated operatively and nonoperatively, the largest cost component was an indirect cost: missed wages at 28.6% and 63.3%, respectively. While the majority of the direct costs of AFx's are accrued in the period immediately following the injury, indirect cost components will regularly be incurred for nearly 5 months and often longer. The degree and duration to which these indirect costs accumulate are novel findings. Future research should no longer neglect reporting on an intervention's impact on the indirect costs of AFx's.